Absolute pitch in Costa Rica: Distribution of pitch identification ability and implications for its genetic basis - Chavarría Soley, Gabriela (2016)
Absolute pitch is the unusual ability to recognize a pitch without an external reference. The current view is that both environmental and genetic factors are involved in the acquisition of the trait. In the present study, 127 adult musicians were subjected to a musical tone identification test. Subjects were university music students and volunteers who responded to a newspaper article. The test consisted of the identification of 40 piano and 40 pure tones. Subjects were classified in three categories according to their pitch naming ability: absolute pitch (AP), high accuracy of tone identification (HA), and non-absolute pitch (non-AP). Both the percentage of correct responses and the mean absolute deviation showed a statistically significant variation between categories. A very clear pattern of higher accuracy for white than for black key notes was observed for the HA and the non-AP groups. Meanwhile, the AP group had an almost perfect pitch naming accuracy for both kinds of tones. Each category presented a very different pattern of deviation around the correct response. The age at the beginning of musical training did not differ between categories. The distribution of pitch identification ability in this study suggests a complex inheritance of the trait.